Explicit Pragmatic Instruction In Teaching English As A Foreign Language - Aufa, Fauzul (English Education Department, Universitas Islam Indonesia, 2011)
Teaching and learning languages involve more than targeting grammatical and lexical knowledge. To achieve communicative competence in English as a Foreign Language (EFL) context, EFL learners need to develop their pragmatic competence which is better taught explicitly in the classroom. This essay argues that while the implicit instruction is reasonably applicable, the explicit pragmatic instruction is more effective to facilitate EFL learners in developing their pragmatic competence.